OMERTA: TANTANGAN PSIKOLOGI SOSIAL PENGUNGKAPAN KEJAHATAN KORUPSI - Rizma Afian Azhiim (Jurnal Kajian Ilmu Kepolisian dan Anti Korupsi, 2026)
The phenomenon of Omerta, or the code of silence, serves as a significant structural barrier in the investigation of corruption crimes in Indonesia. This culture protects corrupt networks through mechanisms that safeguard superiors, colleagues, and organized syndicates, thereby complicating the disclosure of grand corruption cases. This qualitative research aims to dissect the root causes of the Omerta phenomenon within the context of corruption in Indonesia and evaluate the investigative strategies employed by law enforcement, particularly the Corruption Eradication Commission (KPK). Utilizing a case study approach on the e-KTP corruption scandal, the results indicate that Omerta is rooted in strong patronage networks, blind loyalty, and systemic weaknesses in whistleblower protection. A permissive environment and partial legal implementation create a "chilling effect" that perpetuates this silence. This study concludes that dismantling the walls of Omerta requires an integrated strategy through the optimization of Justice Collaborators (JC). Law enforcement must not only be punitive but also capable of providing credible security guarantees and legal incentives for perpetrators who cooperate. Without such strategic interventions, high-level corruption will remain shielded by the impenetrable veil of silence.